RANCANG BANGUN ALAT PEMILAH PADA BIJI BUAH KELAPA SAWIT BERDASARKAN WARNA DAN BERAT - maria ulfah (Jurnal Teknologi Terpadu, 2023)
In the palm oil industry, processing oil palm kernels in the field to improve the quality of palm oil produced is an important activity. Palm kernel harvesting occurs when the oil content is highest and the free fatty acid content is lowest. To maximize the harvest, it is necessary to develop a Sorting Equipment Design on Palm Oil Seeds based on color and weight carried out in Penajam Paser Utara. The purpose of this tool is to detect the maturity level of oil palm kernels with the TCS3200 Sensor, as well as reading the weight of oil palm seeds with the Loadcell Sensor. The main components in making this tool include TCS3200 Sensor and Loadcell Sensor, with other supporting components namely Conveyor, Infrared (IR) Sensor, DC Motor, Servo Motor, and LCD.The results of the IR sensor test had an average error of 0.05 in distance readings, the Loadcell test had an average error of 1.08  in weight readings and the TCS 3200 Sensor had no error in determining the maturity category in oil palm fruit seeds.